Outcomes of Gestational Diabetes Mellitus in Pakistani Mothers: An Experience of a Tertiary Care Hospital - Samina Naseem Khattak; Abid Hussain Shah; Ayesha Imran; Muhammad Irfan Khattak; Khurram Mansoor; Asma Naveed Memon (Journal of Bahria University Medical and Dental College)
Objective: To assess the incidence and outcome of gestational diabetes mellitus (GDM) during pregnancy among sample of Pakistani population. Study Design and Setting: This was an analytic case-control prospective study carried out at two centers (CMH Kharian and PNS Shifa Hospital Karachi) from 1st Jan till 30th July 2021. Methodology Previously healthy mothers were divided into three groups according to their risk of elevated glucose levels gestational diabetes mellitus (GDM) during pregnancy. Associations between GDM eminence (exposure variable) and pregnancy-related, fetal, and neonatal outcomes were reviewed (i.e., mode of delivery, preterm baby, pregnancy-induced hypertension, and fetal macrosomia, stillbirth, premature delivery etc. One way ANOVA was employed to compare the significant differences in different dependent variables amongst three groups. P Values of <0.05 were considered substantial. Results: A total of 120 patients were divided into 3 groups Group 1 (uncontrolled sugar group) who could not achieve adequate sugar control, Group II (adequate sugar control group) and Group III as control group (Non-Diabetic). The mean age in our population was 24 (+ 4.15) years most of study population 70% of mothers were under 25 years of age. The majority (95%) of deliveries in the control group (Euglycemic) were uneventful, but poor fetal outcomes were noted in groups 1 2 (documented to have elevated blood sugars,) especially in the group with Uncontrolled Sugar. GDM was positively associated with preterm birth, stillbirth and macrosomia. Conclusion: GDM is a prevalent disease in Pakistan and needs and has association with poor pregnancy outcomes. Urgent attention requires at individual and state level to reduce morbidity and mortality.